Designing a Social Responsibility Model Based on Health and Welfare for Mazandaran Medical Sciences Employees - Zakariyanezhad1, Zinat; Mehrara, Asadollah; Deiri, Einolah (Iranian Journal of Educational Sociology, 2022)
Purpose: The aim of this study was to design a social responsibility model based on the health and welfare of Mazandaran Medical Sciences employees.Methods: The research design was qualitative, using thematic analysis. The statistical population consisted of experts and elites in the fields of management, human resources, health, and medical sciences at Mazandaran Medical Universities in 2023. A purposive and snowball sampling method was employed, and after conducting 15 in-depth interviews, theoretical saturation was achieved. Data were collected through semi-structured interviews and analyzed through open, axial, and selective coding, based on the six-stage thematic analysis method of Clarke and Brown.Findings: Based on the thematic analysis results, 16 categories were identified, including the proper selection of managers and employees, provision of welfare services, commitment, attitude, having a policy on social responsibilities, laws and regulations, role conflict resolution, support and participation, evaluation, transparency, improvement of working conditions, cultural promotion, supervision, individual characteristics, a value-based perspective on human capital, and awareness, all of which are essential in designing a social responsibility model based on the health and welfare of Mazandaran Medical Sciences employees.Conclusion: The results showed that the social responsibility model based on health and welfare is organized around themes such as employee welfare and health, individual characteristics, cultural promotion, evaluation and supervision, efficient management, organizational attitude and commitment, and regulations.